Characterization of Three Novel SXT/R391 Integrating Conjugative Elements ICEMfuInd1a and ICEMfuInd1b, and ICEMprChn1 Identified in the Genomes of Marinomonas fungiae JCM 18476T and Marinomonas profundimaris Strain D104 - Badhai, Jhasketan; Das, Subrata K. (Frontiers in Microbiology, 2016)
The genus Marinomonas comprises Gram negative bacteria which are widespread in the marine environment and there is no report on the genomic analysis of SXT/R391 ICEs derived from this group of bacteria. This study describes the genomic features of three new SXT/R391 integrating conjugating elements (ICEs) identified in the genome of Marinomonas fungiae JCM 18476T (ICEMfuInd1a and ICEMfuInd1b) and in Marinomonas profundimaris strain D104 (ICEMprChn1). Structural organizations of the three ICEs were similar to the typical SXT/R391 family of ICEs and showed high degree of conservation in the core genes. Sequence analysis revealed ICEMfuInd1b and ICEMprChn1 were inserted into the genome at 5’-end of the typical host prfC gene, while ICEMfuInd1a was inserted at 5’-end of the atypical hipA-like gene. Despite their coexisting, the ICEMfuInd1a and ICEMfuInd1b were not present in a tandem fashion in the genome of M. fungiae. Phylogenetic analyses revealed the three ICEs either evolved independently or high degrees of recombination events had masked their common evolution from SXT-like ancestors. Further, we found that the typical entry exclusion mechanism mediated by the TraG/EeX protein pair was likely defective in preventing the conjugative transfer of a second copy of the same S (SXT) group ICE in M. fungiae due to mutations. Our analysis showed the presence of 16, 25 and 27 variable genes in the hotspots of ICEMfuInd1a, ICEMfuInd1b and ICEMprChn1 respectively, many of which were not reported earlier for SXT/R391 ICEs. Sequence analysis predicted these hotspot regions were shaped by acquisition of genes through homologous recombination between the SXT and R391 related ICEs or mobile genetic elements present in disparate marine bacteria. Multidrug resistance genes which are hallmark feature of SXT/R391 ICEs were not present in either of the two ICEs from M. fungiae but were present within a transposon cassette in the HS-1 of the ICEMprChn1 from M. profundimaris. Finally, our data provided information on the genetic diversity and predicted functions encoded by variable genes present in the hotspot regions of these new ICEs.